Structural legacies and the motherhood penalty: How past societal contexts shape mothers’ employment outcomes in reunified Germany - Collischon, Matthias; Eberl, Andreas; Reichelt, Malte (2020)
Motherhood penalties vary strongly across societal contexts. While most studies that aim to explain such differences focus on institutions, a smaller literature refers to the influence of cultural norms or a complex interaction between the two. Empirically, however, it is yet unclear if such norms play a role and how they—jointly with institutions—contribute to motherhood penalties. We make use of a unique historical setting that allows us to assess how societal contexts affect maternal work preferences and labor market outcomes in the short- and long-run. Germany’s division into socialist East and parliamentary democratic West led to considerably different gender norms. But German reunification in 1990 mostly realigned gendered institutions. Using data from the German Socio-Economic Panel (SOEP), we show that East and West German mothers’ preferred and realized labor force participation and working hours nevertheless remain divergent. We then focus on East German women who moved to the West during and after the country’s transitionary period. Despite moving to a context with more conservative gender norms, East German mothers in the West retain and fulfill their work preferences. Our findings imply that it is the structural legacy of past norms and institutions, not current ones, that shapes maternal work preferences and thus pave the way for motherhood penalties. Moreover, societal norms at the time of childbirth do not directly affect mothers’ labor force participation, working hours, or wages. Gendered outcomes in the labor market are thus highly dependent on institutional and normative changes across cohorts.<br
Keywords: motherhood penalty; gender wage gap; German reunification; work preferences; societal norms; institutions; Gender